Dusp1 modulates activin/smad2 mediated germ layer specification via FGF signal inhibition in Xenopus embryos - Umair, Zobia (Anim Cells Syst (Seoul), 2020)
Activin, a member of the transforming growth factor (TGF-β) superfamily, induces mesoderm, endoderm and neuro-ectoderm formation in Xenopus embryos. Despite several previous studies, the complicated gene regulatory network and genes involved in this induction await more elaboration. We identified expression of various fibroblast growth factor (FGF) genes in activin/smad2 treated animal cap explants (AC) of Xenopus embryos. Activin/smad2 increased fgf3/8 expression, which was reduced by co-injection of dominant negative activin receptor (DNAR) and dominant negative Fgf receptor (DNFR). Interestingly, activin/smad2 also increased expression of dual specificity phosphatase 1 (dusp1) which has been known to inhibit Fgf signaling. Dusp1 overexpression in dorsal marginal zone caused gastrulation defect and decreased Jnk/Erk phosphorylation as well as Smad1 linker region phosphorylation. Dusp1 decreased neural and organizer gene expression with increasing of endodermal and ventral gene expression in smad2 treated AC, indicating that dusp1 modulates germ layer specification. Dusp1 decreased neural gene expression in fgf8 treated AC, suggesting that Erk and/or Jnk phosphorylation may be involved in fgf8 induced neural induction. In addition, dusp1 decreased the reporter gene activities of activin response element (ARE) and increased it for bmp response element (BRE), indicating that dusp1 modulates two opposite morphogen signaling of dorsal (activin/Smad2) and ventral (bmp/Smad1) tracks, acting to fine tune the Fgf/Erk pathway.